Risk Factors of Acute Respiratory Infection in Children Aged 6-12 Years in Urban Areas: A Literature Review Study - Rajebta, Nikita Alia; Arvian, Shenia Rully; Astuti, Winda Dwi; Tanca, Chendy Yugu; Herbawani, Chahya Kharin (Universitas Nahdlatul Ulama Surabaya, 2025)
One disease that affects school-aged children is Acute Respiratory Infections (ARI). Acute Respiratory Infections (ARI) can be caused by various causative agents, such as viruses, bacteria, or even fungi; air pollution from smoke or gas can also cause Acute Respiratory Infections (ARI). The method used in preparing this article is a literature review. Article or journal searches were conducted on five databases: Mendeley, PubMed, ScienceDirect, Google Scholar, and Garuda. The keywords used in Mendeley, Google Scholar, and Garuda were